Milly, Molly and the runaway bean - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2004)
Milly and Molly learn the importance of good nutrition when they grow a bean plant that helps a sick boy get better. Suggested level: junior